Aqueous phase environmental friendly organic corrosion inhibitors derived from one step multicomponent reactions: A review - Verma C.; Haque J.; Quraishi M.A.; Ebenso E.E. (My University, 2025)
Use of organic compounds as corrosion inhibitors is one of the most profitable, effective and ease methods because of their simplicity and cost-effective synthesis using commercially available inexpensive starting materials. Nowadays, the synthesis of corrosion inhibitors using traditional multistep reactions is highly restricted because of the increasing demands of “green chemistry” and sustainable technology because the traditional syntheses are associated with several workups and purification steps that results into the discharge huge amount of environmental malignant chemicals into the surrounding environment. In contrast, the widely accepted multicomponent reactions (MCRs) have developed as a new greener tool for the synthesis of variety of compounds that have several biological and industrial applications. Nowadays, the scientist working in the field of corrosion is also looking towards the development of environmental-friendly corrosion inhibitors. In last few years, numerous organic compounds synthesized using bi-component and multicomponent reactions and investigated are investigated as effective corrosion inhibitors for metals and alloys. Present review article features the collection of earlier works that have been carried out on the topic “corrosion inhibitors derived from bi-component reactions (BCRs) and multi-component reactions (MCRs)”. © 2018